Analysis Concept of a Mosque-Based Community Economic Empowerment Strategy at the Islamic Center Dato Tiro Bulukumba - Ega Rusanti; A Syathir Sofyan; Syarifuddin Syarifuddin (JESI (Jurnal Ekonomi Syariah Indonesia), 2021)
The purpose of this research is to find out and analyze the concept of mosque- based economic empowerment at Dato Tiro Islamic Center in Bulukumba Regency which has been and should be carried out. The research conducted is a qualitative study with field research (field studies) in the deepening of the reference as a source of primary and secondary data, while in the collection of data used methods of observation, interviews and documentation. The results of the study show that the concept of empowerment that is being applied today such as the use of a multipurpose floor as a market area every Friday is effective enough for the community and the prosperity of the mosque. It's just that there are many other potential possessed by the mosque that can be developed in an effort to empower the Ummah, establishing BMT as a form of financial assistance to the community in building a business. So that the mosque is able to carry out its function not only as a means of worship but also has a role in building the economy of the Ummah.